Carbon footprints and personal emission monitoring - Perrels, Adriaan; Katajajuuri, Juha-Matti (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
To reach the long-term goal of substantially reducing greenhouse gas emissions, the consumption of households is a crucial factor. To address consumers and change their behaviour towards a more climate-friendly lifestyle, new policy instruments are needed